Synthesis of flower-like AgI/Bi5O7I hybrid photocatalysts with enhanced photocatalytic activity in rhodamine B degradation. Issue 16 (28th June 2018) - Jiang, Xiaole; Ma, Yueying; Zhao, Chunran; Chen, Yijing; Cui, Min; Yu, Jingxiong; Wu, Ying; He, Yiming
Abstract: Abstract : Flower-like AgI/Bi5 O7 I hybrid photocatalysts were fabricated via a hydrothermal method and the subsequent heating process with AgI/Bi4 O5 I2 as the intermediate. X-ray powder diffraction, Raman, X-ray photoelectron spectroscopy, diffuse reflectance spectra, scanning electron microscopy, transmission electron microscopy, photoluminescence, and electrochemical methods were used to reveal the structure, elemental content, morphology, and charge separation capabilities of the as-prepared samples. The photocatalytic test showed that the AgI/Bi5 O7 I composites own much higher photoactivity than pure AgI and Bi5 O7 I. Based on the result of XPS analysis, the composite is believed to be the Ag/AgI/Bi5 O7 I system. Due to the suitable band potentials of AgI and Bi5 O7 I, the ternary system can form a heterojunction structure which works in a Z-scheme mechanism with Ag nanoparticles as the transfer media. The guided charge transfer in the composite prolongs the life time of charge carriers and eventually leads to the high photocatalytic activity of AgI/Bi5 O7 I. Additionally, the flower-like structure of the composite also contributes to the photocatalytic reaction.